Resurgence of vaccine-preventable diseases in Venezuela as a regional public health threat in the Americas (2019)
Venezuela’s tumbling economy and authoritarian rule have precipitated an unprecedented humanitarian crisis. Hyperinflation rates now exceed 45,000%, and Venezuela’s health system is in free fall. The country is experiencing a massive exodus of biomedical scientists and qualified healthcare professionals. Reemergence of arthropod-borne and vaccine-preventable diseases has sparked serious epidemics that also affect neighboring countries. In this article, we discuss the ongoing epidemics of measles and diphtheria in Venezuela and their disproportionate impact on indigenous populations. We also discuss the potential for reemergence of poliomyelitis and conclude that action to halt the spread of vaccine-preventable diseases within Venezuela is a matter of urgency for the country and the region. We further provide specific recommendations for addressing this crisis. © 2019 Centers for Disease Control and Prevention (CDC). All rights reserved.